Taxonomies for Sustainable Finance - Fernández Moscol, Mercedes (2025)
The purpose of this article is to provide an introduction to the status of taxonomies for sustainable finance, summarizing their origin, theircontent in Europe and some Latin American countries, and, in particular, their status in Peru. Similarly, some of the benefits that can be achievedby having a taxonomy are presented.